Groundwater Arsenic in an Urban Area: Izmir’s Comprehensive Response and Remediation Blueprint - Baba, Alper; Kırçiçek, N.T.; Güngör, E.B.; Baba, A. (Springer Science and Business Media Deutschland GmbH, 2025)
The contamination of groundwater with arsenic poses a critical challenge to the environment and public health, affecting millions of people worldwide. In the rapidly urbanising regions of Türkiye, understanding the origin, mobility and effective treatment of arsenic contamination is crucial to ensure water safety. This study analyses the spatial distribution of arsenic contamination of groundwater, specifically in the province of İzmir, while attempting to delineate the potential sources of risk. The arsenic concentrations in groundwater samples from different districts were analysed, and the variations at district level were visualised using a point-based density map. The resulting values were then critically compared with the World Health Organization (WHO) limits and Turkish national regulations (10 μg/L) to draw attention to the pronounced spatial differences in concentrations. Following the arsenic crisis in 2008, the İzmir Municipality has taken a decisive course and implemented targeted arsenic remediation strategies that represent significant progress in solving and addressing this pervasive problem. In 2023 alone, more than 139 million m3 of groundwater were treated, accounting for almost 30% of the city’s drinking and industrial water supply. This considerable magnitude represents a remarkable level of implementation, especially against the backdrop of numerous global cities struggling with similar contamination problems. The results of this study should serve as a basis for sustainable groundwater management strategies, not only for İzmir, but also for other regions with hydrogeological and urban dynamics. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Keywords: Arsenic Contamination; Groundwater Quality; Sustainable Water Management; Türkiye; İzmir